Engaging with intelligent voice assistants for wellbeing and brand attachment - Prentice, C. (2023)
The study draws upon the theories of self-determination and motivation of expectancy to examine how intrinsic motives drive consumers to engage with artificial intelligence (AI) powered intelligent voice assistants (IVAs). The study also explores how consumer engagement leads to their wellbeing and attachment to these AI gadgets and their associated brands. Engagement in this study refers to consumers’ usage and involvement with IVAs. Subject wellbeing was modeled as a mediator between consumer engagement and brand attachment. The research was conducted in the USA with respondents who had owned and used at least one type of IVAs (e.g., Siri, Google Home, Alexa). A range of statistical procedures including structural equation modeling were undertaken to assess the proposed relationships. The results show that the consumer’s need for autonomy, sense of competence, and relatedness are significantly related to IVA engagement. Consumer wellbeing also had a significant mediation effect on the relationship between engagement and brand attachment. The study is the first to link consumer engagement, individual wellbeing, and brand attachment. The study contributes to positive psychology and branding research by integrating mental health and branding effects. The findings have implications for marketing and psychology practitioners.